Estudo experimental das alterações agudas na glicemia e concentrações testiculares de ATP e glicose induzidas por torção unilateral, in vivo - Guimarães, Sérgio Botelho (2002)
Spematic cord torsion is one of the more common surgical urological emergencies in childhood. An experimental study has been conducted to investigate acute changes in testicular concentrations of ATP and glucose following one-hour unilateral 720º testicular torsion. Sixty prepubertal male Wistar rats were distributed into two groups: Group 2(Ischemia) and Group 1(Sham operated). Each group(n=30) was divided into 5 subgroups (n=6). All animals were subjected to right testicular torsion of 720º. The testicular torsion of animals from Group 1 was immediately corrected. Group 2 animals had their testicular torsion lasting one hour followed by detorsion. Testicles were collected and arterial blood samples taken from abdominal aorta of each animal subgroup at the and of ischemic period or one hour after sham operation and 0.5, 1,6 and 24 hours later. ATP and glucose concentrations were significantly decreased (p<0,05) in ischemia group as compared to sham group at the end of ischemic period. There was no difference in glycemia when comparing ischemic versus sham-operated rats. Glucose concentrations were significantly increase (p<0,05) in ipsilateral testis of sham-operated rats No significant change in ATP and glucose concentrations were found in the left testicle in comparasion to the ones measured in the rigth testicle of the same animal. The decrease in ATP and glucose concentrations may be explained by the reduction in blood flow to the torted testis imposed by torsion. The absence of significant contralateral alterations in the concentrations of ATP and glucose could be related to the limited time of isquemia imposed to the right testis. It is concluded that unilateral one-hour testicular torsion causes a decrease in ipsilateral testicular perfusion resulting in decresead testicular concentrations of glucose and ATP in the ipstelial (right) testicles and no alterations in the concentrations of glucose and ATP in the contraleral testicles. Simple testicle manipulation (Sham Operation) causes a signficant increase in glucose concentrations in the ipsilateral(right)testis.